Transcriptional profiling of breast cancer‐associated lymphatic vessels reveals VCAM‐1 as regulator of lymphatic invasion and permeability. Issue 10 (8th August 2019) - Dieterich, Lothar C.; Kapaklikaya, Kübra; Cetintas, Timur; Proulx, Steven T.; Commerford, Catharina D.; Ikenberg, Kristian; Bachmann, Samia B.; Scholl, Jeannette; Detmar, Michael
Abstract : Tumor‐associated lymphangiogenesis and lymphatic invasion of tumor cells correlate with poor outcome in many tumor types, including breast cancer. Various explanations for this correlation have been suggested in the past, including the promotion of lymphatic metastasis and an immune‐inhibitory function of lymphatic endothelial cells (LECs). However, the molecular features of tumor‐associated lymphatic vessels and their implications for tumor progression have been poorly characterized. Here, we report the first transcriptional analysis of tumor‐associated LECs directly isolated from the primary tumor in an orthotopic mouse model of triple negative breast cancer (4T1). Gene expression analysis showed a strong upregulation of inflammation‐associated genes, including endothelial adhesion molecules such as VCAM‐1, in comparison to LECs derived from control tissue. In vitro experiments demonstrated that VCAM‐1 is not involved in the adhesion of tumor cells to LECs but unexpectedly promoted lymphatic permeability by weakening of lymphatic junctions, most likely through a mechanism triggered by interactions with integrin α4 which was also induced in tumor‐associated LECs. In line with this, in vivo blockade of VCAM‐1 reduced lymphatic invasion of 4T1 cells. Taken together, our findings suggest that disruption of lymphatic junctions and increased permeability via tumor‐induced lymphatic VCAM‐1 expression may represent a new target to block lymphatic invasion and metastasis. Abstract : What's new? Tumor‐associated lymphatic vessels serve important roles in tumor progression and metastasis. Nonetheless, little is known about the molecular changes in these vessels that give rise to a tumor‐promoting phenotype. In this study, transcriptional analysis was performed on lymphatic endothelial cells (LECs) isolated from a mouse model of triple‐negative breast cancer. Endothelial adhesion molecules, including tumor‐induced VCAM‐1, were strongly upregulated in tumor‐associated LECs. Additional experiments showed that VCAM‐1 upregulation influences lymphatic permeability and that its inhibition attenuates lymphatic breast cancer cell invasion. The findings identify VCAM‐1 as a potential target for the blockade of lymphatic invasion of tumor cells.